The legislative work in an authoritarian regime: the case of the São Paulo administrative department - Codato,Adriano (2014)
This article describes the legislative process of the Administrative Department of the state of São Paulo (DAESP) during the Estado Novo dictatorship and seeks to answer three questions: i) what were its real attributions? ii) what was its place among the state-level government agencies? iii) what was its role in the dictatorial regime's public decision-making structure? Ordering and interpreting information on the DAESP's deliberative process will allow us to establish whether or not it exercised power (understood as the capacity by those who controlled it to impose their preferences), what was the magnitude of this power, what type of power was exercised, over what and whom. The frequency of its meetings, the coordination of the agendas of the dictatorial State's apparatuses involved in the decision chain, the activism of each councillor of DAESP and a sample of the legal opinions produced by it between 1939-1947 were all analysed. The findings can be summarised into three propositions: i) DAESP was not a decision-making arena per se as it did not make important decisions, but instead produced a huge amount of decisions regarding the formal aspects of the decree-laws issued by the Interventoria Federal (appointed governors); ii) therefore, the president of the DAESP did not have greater political or bureaucratic power than the interventor, and iii) although the Department mimicked some legislative routines, it cannot be considered a substitute of the state legislature.